Perbuatan Melawan Hukum Dilihat Berdasarkan Perspektif Hukum Perdata dan Pidana - Zainudin Hasan; Rohizad Olivia Watuna (Terekam Jejak Publisher, 2024)
Unlawful acts are actions that are identified as violating the law or statute so that they have legal consequences. Therefore, it is important to understand the legal regulations and juridical theories regarding unlawful acts and how to resolve them, especially in court. Acts against the law can be seen from the perspective of criminal law and civil law. In criminal law, unlawful acts are known as wederrechtelijk, namely actions that violate the Criminal Code (KUHP). One of the elements of a criminal act is the element of unlawfulness which is included in the formulation of the offence and is the core part of the offence, which is specifically called unlawfulness (for example Article 372 of the Criminal Code). Meanwhile, breaking the law as an element that is not mentioned in the formulation of the offence but is the basis for imposing a crime is called breaking the law in general (for example Article 351 of the Criminal Code). In civil law, unlawful acts are known as onrechtmatigedaad, namely actions that violate the Civil Code (KUHPer). Article 1365 of the Civil Code states that every unlawful act that causes harm to another person requires the perpetrator to compensate for the loss. It is essential to identify the elements of an unlawful act to determine whether it is unlawful.